Transitional civic placemaking: dispersed initiatives in changing urban landscapes - Tang, Bo; Mitchell, Maurice (Architecture of Rapid Change and Scarce Resources, 2019)
Field trip publication on the theme of "Transitional Civic Placemaking: Dispersed Initiatives in Changing Urban Landscapes" in Athens, Calabria and Freetown (and Yakutsk). Produced by students from MArch/MA by Project Unit 6 and Degree Studios 3 & 7 at the Cass School of Art, Architecture and Design at London Metropolitan University in 2018-19. Tutors: Maurice Mitchell, Bo Tang, Robert Barnes, Sandra Denicke-Poulcher and Jane McAllister.